(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2022)
For the safety of buildings and institutions that are established on weak or collapsing soils(sand and clay) characterized by high permeability and continuous subsidence, it has become necessary to improve and strengthen the soil. In this theoretical research, the focus was on the method of soil injection with the jet grout system through modeling models of clay and sandy soils with different geometrical properties dimensions (10 m x10m) based on the PLAXIS 3D 2020 program, load displacement curve was calculated and the soil bearing capacity was calculated on the shallow Foundation with dimensions (1m x1m) by injecting a single jet grout column with (D = 0.5 m) and ( L =10 m). The result of the improvement in bearing capacity was noticeable after injecting the jet grout column for clay soil types (soft, medium, and stiff) as well as for sandy soil types (loose, medium, and dense).